Spatial change analysis, Analysis of Spatial patterns changes in rainy season over Iran - Maryam Sanaei; Gholamreza Barati; Alireza Shakiba (تحقیقات کاربردی علوم جغرافیایی)
Climate change, including spatial changes in rainfall following the increase in greenhouse gases, is a challenge that affects various aspects of life in human societies today. In this study, the long-term spatial changes of the rainy season from September to May were studied using the statistics of "local Moran" and "Hot spots of Getis Ord-J" during 5 5-year periods from 1991 to 2015. The application of local Moran statistics showed that areas with long rainfall periods are in good agreement with the countrychr('39')s rainfall pattern. This adaptation is accompanied by a negative spatial correlation in lands with short rainfall periods. The pattern obtained from the hot spot statistics also showed itself to be more consistent and corresponded to two very low rainfall regimes in the southeast and center, while according to local Moran statistics, this pattern was more scattered and parts of it had a low southern precipitation regime. . In addition, the results of Alexandersonchr('39')s statistics to identify mutations in the long-term series of the rainy season showed that the time series of 13 stations out of 108 stations studied experienced a sudden jump that these mutations are more in the southern stations in the country and in later years. It has occurred since 2000 AD.